The Influence of Halal Lifestyle, Fashion Trends, and Viral Marketing on Gen Z Muslim Fashion Purchasing Decisions - Eva Yulia Ningsih; Muhammad Ersya Faraby (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Seeing the condition of Indonesian society, which is predominantly Muslim, presents a great opportunity for the development of Muslim fashion because the interest of every Muslim in Muslim fashion products is starting to increase, and the advancement of technology has also helped in the marketing of Muslim fashion products. This research aims to analyze the influence of halal lifestyle, fashion trends, and viral marketing on the purchasing decisions of Muslim clothing by generation Z in Bangkalan City. This research uses a quantitative method with multiple linear regression analysis techniques and classical assumption tests. The data used are primary data collected through the distribution of questionnaires. The research sample consisted of 107 respondents who met certain criteria using purposive sampling technique. The research results show that halal lifestyle and viral marketing partially influence purchasing decisions, while fashion trends do not affect the purchasing decisions of Muslim clothing. The coefficient of determination test results showed that halal lifestyle, fashion trends, and viral marketing simultaneously have a 48.6% influence on the purchasing decisions of Muslim clothing. This research can provide insights to Muslim fashion business practitioners to develop more effective marketing strategies to succeed in the Muslim fashion market.